Clinical Efficacy and Safety of ‘Oxy +’ in Type 2 Diabetes: A Pilot Study - Alam, Md Anzar; Ahad, Mariyam; Quamri, Mohd Aleemuddin; Ansari, Fasihur Rehman; Parveen, Farooqui Shazia (International Journal of Human and Health Sciences (IJHHS), 2020)
Background and objectives: Diabetes is a common metabolic disorder.Type 2 diabetes accounts for the vast majority of around 92% of the population worldwide. Long term hyperglycemia leads to macro and microvascular complications. Oxy+ is a nutraceutical capsule which contains mainly Arthrospira (spirulina). Most of the diabetic people use it. Hence a clinical trial was conducted to evaluate the clinical efficacy and safety of Oxy + in Type 2 Diabetes. Material Methods: The study was designed as a single-blind pilot study; 10 eligible patients of type 2 diabetes were allocated. Oxy+ was given in capsule form; 2 capsules twice daily orally for 45 days after the meal. Test drug was evaluated on subjective parameters at 0th, 15th, 30th and 45th days whereas objective parameters were assessed before and after the treatment. The results of the intervention were analyzed using suitable statistical methods. Results and Observation:The study effects on subjective parameters like polyuria, tiredness, polyphagia, polydipsia, and Tingling Sensation were found significantly reduced. The objective parameters were assessed before and after as Mean ± SD for FBS (164.4±36.019 vs 111.1±25.075), PPBS (248.5±51.70 vs 170.1±45.148) and HbA1c (9.14±1.517 vs 6.95±1.224).The results were analyzed after using paired‘t’ test. Interpretation and Conclusion:The findings about both parameters (subjective and objective) that the ‘Oxy+’ is effective in type 2 diabetes and the cure was considerable. Safety parameters (SGOT, SGPT, Blood Urea, and Serum Creatinine) were remained unchanged. Therefore, it can be concluded that the ‘Oxy+’ would be safe and effective in the management of type 2 diabetes. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 96-100